Novel 99mTc-Radiolabeled Anionic Linear Globular PEG-Based Dendrimer-Chlorambucil: Non-Invasive Method for In-Vivo Biodistribution - Ghoreishi, Seyedeh Masoomeh; khalaj, Ali; Bitarafan-Rajabi, Ahmad; Azar, Amir Darbandi; Ardestani, Mehdi Shafiee; Assadi, Artin (Drug Research, 2017)
Chlorambucil (CBL) is an alkylating agent, which widely use in the treatment of various types of tumors. The main purpose of this study is to evaluate the in-vivo biodistribution of CBL conjugated to the anionic dendrimer, which has a great ability to labeled with 99mTc through binding to carboxylate terminate groups. Whole body scans were used to analyze the percentage of the injected dose in different times. Radiochemical purity (RCP) and in-vivo biodistribution were also calculated with the SPECT/CT instrument. Our study proposes a new method for RCP determination and shows that this carrier is a promising agent to complex with the 99mTc and biological assessment.
Keywords: dendrimer; chlorambucil; labeling; region-of-interest